Thomas goes fishing - Awdry, Rev. W.; Courtney, Richard, 1955-; Awdry, W. (New York : Random House, 2005)
Envious of the children who are fishing in the river near the railroad tracks, Thomas the tank engine finds a way to enjoy the same activity.
"Thomas the Tank Engine & friends"--Copyright p.
Based on The railway series by the Rev. W. Awdry.
"A Britt Allcroft Company production"--Copyright p.
Preschool-kindergarten
Keywords: Railroads -- Trains -- Fiction; Fishing -- Fiction